Surrogacy in India: Legal, Ethical, and Social Dimensions - kaur, Ramneet; Sharma, Tanvi; Minhas, Pallavi; Kaur, Jagjit; Sekhon, Nyamat (Journal of Neonatal Surgery, 2025)
The concept of family has played a significant role in shaping civilization, with marriage and procreation being at the core of social structures. However, infertility has become a growing concern, affecting individuals across different demographics. Advances in assisted reproductive technologies (ARTs) have introduced surrogacy as a solution, yet it remains entangled in ethical, legal, and social debates. India, once a global hub for commercial surrogacy, has shifted towards strict regulation, banning commercial surrogacy while allowing altruistic surrogacy under specific conditions. This paper critically examines the legal framework regulating surrogacy in India, including the Surrogacy (Regulation) Act, 2021, and its impact on intended parents, surrogate mothers, and marginalized groups. It also explores judicial interventions, the exclusion of LGBTQIA+ individuals and single parents, and the ethical concerns surrounding the ban on commercial surrogacy. The study further evaluates global surrogacy laws and suggests reforms for a more inclusive and ethical approach